Propuesta de estrategia de fidelización a través del marketing relacional para una micro empresa del sector metalmecánico: caso de estudio Industrias Cadus Ltda (2020)
This case study aims to provide a proposal of loyalty strategy for the company Industrias Cadus Ltda, through relational marketing that aims to convert any service, sale or contact with customers into lasting relationships based on the satisfactions of their needs, demands and preferences. Initially, a diagnosis of the current situation of the microenterprise is made, to know the context of the organization through the analysis of its value chain and the EFE and EFI arrays are applied. Subsequently, this research is developed from a model based on relational marketing of a model proposed by Josep Alet and Juan Carlos Alcaide.